(untitled) (LEARNing Landscapes, 2010)
This work provides insight into the experience of a group of Aboriginal and non-Aboriginal educators and their sense of responsibility. This involves discussions concerning the use of found poetry as well as how found poetry aided in fashioning an interpretation of educator’s experience of the hôte: a guest-host who accommodates and negotiates the difference of others and self.